Retraction Note to: An investigation on the properties of SnO2 nanoparticles synthesized using two different methods (Journal of Materials Science: Materials in Electronics, (2014), 25, 1, (303-310), 10.1007/s10854-013-1586-3) - Shalan, A. E.; Osama, I.; Rashad, M. M.; Ibrahim, I. A. (Journal of Materials Science: Materials in Electronics, 2023)
The Editor-in-Chief has retracted this article due to irregularities in figures in this article. Specifically: In Fig. 5A, particles created using different methods show an N2 adsorption–desorption isotherms with the same shape after vertical scaling and shift. In Fig. 5B, in the co-precipitation method at 600°C and 800°C, the pore size distributions appear to be identical. In Fig. 5A, particles created using different methods show an N2 adsorption–desorption isotherms with the same shape after vertical scaling and shift. In Fig. 5B, in the co-precipitation method at 600°C and 800°C, the pore size distributions appear to be identical. The Editor-in-Chief has therefore lost confidence in the veracity of the results presented in this article. A. E. Shalan does not agree to this retraction. I. Osama, M. M. Rashad and I. A. Ibrahim have not responded to any correspondence from the editor/publisher about this retraction.
CRIS-Team Scopus Importer:2023-12-01